Penerapan Algoritma Floyd-Warshall pada Jalur Evakuasi Korban Kecelakaan di Boyolali - Fitri Nofita Sari; Juhari Juhari; erna Herawati (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
The Floyd-Warshall algorithm is one of the algorithms that can be used to solve the shoetest route problem and is the easiests to apply because it can find all the shortest routes between each possible pair of position and is part of a dynamic program that is very efficient in solving optimal route promblems. The Floyd-Warshall algorithm works by comparing each possible path on the graph for each node pair and checking the resulting node combination. The problem of the shortest route in daily life is the evacuation of victims of traffic accidents in Boyolali, Central Java. For evacuation to be more effective, a nearby route to the nearest hospital is needed. Based on the results of the research that has been done, it can be concluded that the study produced reference matrix in the form of the shortest trajectory used to determine the shortest route to nearest hospital in Boyolali, Central Java.